Development of mobile application to improve the communication ability of autism spectrum disorder children - Rahmi Putri, Zulma Indra; Khaldun, Yanuar; Saputri, Toviyani Widi; Jamaludin, Amat; Pujaningsih (Jurnal Pendidikan Bitara UPSI, 2025)
Children with communication disabilities have difficulty communicating with others, making it difficult to socialize with the people around them. To address this issue, various assistive tools have been developed. However, most existing tools have several limitations, such as being traditional, non-portable, offering a limited selection of sentences, and being available only in English. These limitations hinder children from adding new sentences and make the tools inaccessible to non-English speakers, particularly Indonesian users. Therefore, this study aims to develop a mobile application, Katakan yang Kamu Ingin (KKI), according to the needs of children with autism spectrum disorder and to assess changes in their communication skills after using the application. This study employed Richey and Klein’s Design and Development Research method to develop the mobile application KKI. The participants were two nonverbal children with ASD from a special education school. The resulting product was an Android-compatible APK featuring customizable sentence categories and user-friendly audio-enabled communication options. The application also contains menu items such as a selection of sentences commonly used for communicating in a school environment, and the function of adding sentences by the user. Following validation by three expert evaluators, the results indicate that the product is highly feasible, with revisions based on expert suggestions. Observational data on communication performance in subjects A and B show improvements in communication skills across the initial baseline, intervention, and final baseline phases. These findings demonstrate that the KKI mobile application can positively impact the communication abilities of nonverbal ASD children, making it an effective tool for supporting communication in a school setting.